2018
DOI: 10.4103/ccd.ccd_562_17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a calcium sucrose phosphate based toothpaste in elevating the level of calcium, phosphate ions in saliva and reducing plaque: A clinical trial

Abstract: Aim:To evaluate and compare the efficacy of “calcium sucrose phosphate” (CaSP) toothpaste (Enafix 5%) with ordinarily used calcium, phosphate-containing toothpaste in elevating the level of calcium, phosphate ions in saliva. Secondary aims were to evaluate substantivity and plaque-reducing ability of CaSP toothpaste.Materials and Methods:Thirty study participants of age group 6–13 years were divided into two groups: Group X (Control group) was made to continue brushing with their regularly used calcium, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Menon et al . [ 12 ] concluded that a salivary quantity of calcium experiences a striking augmentation with CaSP causing higher calcium accretion on the dentition. Additionally, CaSP reduces plaque deposition on the tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Menon et al . [ 12 ] concluded that a salivary quantity of calcium experiences a striking augmentation with CaSP causing higher calcium accretion on the dentition. Additionally, CaSP reduces plaque deposition on the tooth surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…It provides freely available calcium and phosphate ions at concentrations significantly higher than those normally present in the saliva at pH values found in the oral cavity. [18][19][20][21] CSP acts as a cariostatic agent through different mechanisms and prevents development of WSLs.…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered that bromelain inhibits the production of bio lms by preventing bacterial attachment to. Tadikonda A 23 conducted Clinical trials with toothpaste containing bromelain, and demonstrated improved plaque and gingivitis scores and extrinsic enamel stain removal capabilities.…”
Section: Group IV Bromelain Group (Rocs)mentioning
confidence: 99%